2021
DOI: 10.3390/w13111468
|View full text |Cite
|
Sign up to set email alerts
|

Using Optimal Environmental DNA Method to Improve the Fish Diversity Survey—From Laboratory to Aquatic Life Reserve

Abstract: Conserving aquatic ecosystems requires efficient tools to accurately assess the biodiversity of aquatic species. However, existing knowledge is insufficient in terms of the reliability and the comparability of methods measuring fish diversity. Environmental DNA (eDNA), as a promising method, was used to detect fish taxa in this study. We optimized the eDNA method in the laboratory, and applied the optimal eDNA method to survey fish diversity in a natural aquatic life reserve. We simulated necessary steps of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Many studies have now confirmed the strengths of eDNA metabarcoding for local detection of species and, thus community composition inference (Hansen et al, 2018). Similarly to analogous studies (Cilleros et al, 2019; Fraija‐Fernández et al, 2020; Jeunen, Knapp, et al, 2019; Jo et al, 2019; Larson et al, 2022; Li et al, 2021; Turon et al, 2022), our eDNA metabarcoding study confirm that fish community composition and biodiversity patterns can be reliably estimated using this approach.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have now confirmed the strengths of eDNA metabarcoding for local detection of species and, thus community composition inference (Hansen et al, 2018). Similarly to analogous studies (Cilleros et al, 2019; Fraija‐Fernández et al, 2020; Jeunen, Knapp, et al, 2019; Jo et al, 2019; Larson et al, 2022; Li et al, 2021; Turon et al, 2022), our eDNA metabarcoding study confirm that fish community composition and biodiversity patterns can be reliably estimated using this approach.…”
Section: Discussionsupporting
confidence: 88%
“…These kits are less expensive, easy to use and have efficient PCR amplification and also they do not contain any harmful chemical. Hence, they are regarded as best option for extracting e-DNA (Li et al, 2021,). It is evidently known that in both lentic and lotic habitats sediments present in water interfere with the detection of e-DNA from water samples (Goldberg et al, 2011).…”
Section: Extraction Of E-dnamentioning
confidence: 99%
“…Increasing the sampling effort will increase the amount of biodiversity detected, and a threshold must be determined for an optimal sampling volume of eDNA . Up until now, sampling efforts of eDNA have profoundly varied between studies, ranging from 15 mL to 60 L, , which hinders the comparability of biodiversity estimates. A recent paper proposed adjusting the sampling effort to the size or volume of the aquatic ecosystems with a spatial-explicit river flow model .…”
Section: Introductionmentioning
confidence: 99%